PIECES ANALYSIS IN THE INFLUENCE OF THE DESIGNING DIGITAL SIGNATURE CERTIFICATE SYSTEM - Ida Bagus Gede Sarasvananda; I Putu Eka Giri Gunawan; I Komang Arya Ganda Wiguna; Made Suci Ariantini; I Gede Iwan Sudipa (Institute of Computer Science (IOCS), 2022)
Correspondence is an inseparable part of an agency, both private and government. The administration of correspondence has often utilized information system technology in assisting business processes carried out by parties within the organization itself. For example, the Institute for Innovation and Creativity Development (LPIK) of the Indonesian Institute of Business and Technology (INSTIKI) has implemented a correspondence information system, but there is a weakness in the system, namely that there is no digital signature process so that it is not optimal in facilitating the management of correspondence. This study aims to analyze the business processes of the system that is already running using the PIECES (Performance, Information, Economy, Control, Efficiency, Service) method. The benefits of the research are obtained from the analysis of the problems based on the previously running system seen from the use case diagram design, activity diagrams and system interfaces. This results in an analysis of the proposed system to complete system features and system functionality based on the results of the analysis of 6 aspects of PIECES which can assist LPIK institutions in facilitating the mailing business process.